Digitalization, Business Potential, and Financial Inclusion: Youth Training in Parangloe Subdistrict, Gowa Regency - Indra, Dolly; Syahnur, Muh. Haerdiansyah; Lilis Nur Hayati (STIE Amkop Makassar, Indonesia, 2024)
Digitalization is the process of converting physical data or media into a digital format that can be managed using information technology. In Gowa Regency, South Sulawesi, the expansion of IT infrastructure is enhancing public services and improving interactions between citizens and the government. Digitalization offers numerous benefits, such as increased efficiency in information retrieval, easier market access, and expanded market reach, which can boost the economic potential of residents, including those in Parangloe Subdistrict. This Community Service Program (PkM) aims to enhance digital skills among the youth in youth organizations in Parangloe Subdistrict. The training is designed to help the youth become economically independent and promote financial inclusion. The program includes training on creating social media accounts, setting up e-commerce accounts, using Canva, and basic computer literacy. The program will be conducted in July 2024, with prior preparations and socialization with village officials and youth organization leaders. The results indicate that the training exceeded participation targets and improved participants' understanding of digitalization. Overall, the program successfully equipped participants with valuable digital skills, contributing to broader technological and economic inclusivity.